Plasma metabolites Xanthine, 4-Pyridoxate, and d-glutamic acid as novel potential biomarkers for pulmonary tuberculosis - Huang, Huai; Shi, Li-Ying; Wei, Li-Liang; Han, Yu-Shuai; Yi, Wen-Jing; Pan, Zhi-Wen; Jiang, Ting-Ting; Chen, Jing; Tu, Hui-Hui; Li, Zhi-Bin; Hu, Yu-Ting; Li, Ji-Cheng (Clinica chimica acta, 2019)
The lack of rapid and efficient diagnostic methods has been one of the most frustrating challenges in controlling the pulmonary tuberculosis (TB) epidemic. This study was aimed to identify novel non-invasive biomarkers for pulmonary TB. The subjects in this study were divided into four groups: the pulmonary TB group, the community-acquired pneumonia (CAP) group, the lung cancer (LC) group, and the normal control (NC) group. Plasma small molecule metabolites were investigated in each group by using ultra-high performance liquid chromatography coupled with Q Exactive mass spectrometry. Multivariate statistical methods and bioinformatics were used to analyze the data. We identified three differential plasma metabolites such as, Xanthine, 4-Pyridoxate and d-glutamic acid in the pulmonary TB group, compared to the other groups (CAP, LC and NC). The pathway enrichment analysis indicated that the energy source in pulmonary TB was multi-center, which might be involved in maintaining the reproductive ability and virulence of Mycobacterium tuberculosis. The results suggested that Xanthine, 4-Pyridoxate, and d-glutamic acid may serve as potential biomarkers for pulmonary TB. The present study provides experimental basis for developing potential biomarkers of pulmonary TB. •Plasma metabolic profiling has great potential to distinguish pulmonary TB from NC, CAP and LC.•Xanthine, 4-Pyridoxate, and d-Glu might be the novel potential biomarkers for pulmonary TB.•The energy conversion of pulmonary TB presents a multi-center source which maintains the MTB's reproduction and virulence.